High prevalence and magnitude of rapid weight loss in Mixed Martial Arts athletes - Hillier, M.; Sutton, L.; James, L.; Mojtahedi, D.; Keay, N.; Hind, K. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
The practice of rapid weight loss (RWL) in mixed martial arts (MMA) is an increasing concern but data remain scarce. The aim of this study was to investigate the prevalence, magnitude, methods, and influencers of RWL in professional and amateur MMA athletes. MMA athletes (N = 314; 287 men and 27 women) across nine weight categories (strawweight to heavyweight), completed a validated questionnaire adapted for this sport. Sex-specific data were analyzed, and subgroup comparisons were made between athletes competing at professional and amateur levels. Most athletes purposefully reduced body weight for competition (men: 97.2%; women: 100%). The magnitude of RWL in 1 week prior to weigh-in was significantly greater for professional athletes compared with those competing at amateur level (men: 5.9% vs. 4.2%; women: 5.0% vs. 2.1% of body weight; p < .05). In the 24 hr preceding weigh-in, the magnitude of RWL was greater at professional than amateur level in men (3.7% vs. 2.5% of body weight; p < .05). Most athletes "always" or "sometimes" used water loading (72.9%), restricting fluid intake (71.3%), and sweat suits (55.4%) for RWL. Coaches were cited as the primary source of influence on RWL practices (men: 29.3%; women: 48.1%). There is a high reported prevalence of RWL in MMA, at professional and amateur levels. Our findings, constituting the largest inquiry to date, call for urgent action from MMA organizations to safeguard the health and well-being of athletes competing in this sport.